Intimate Partners in Crime: Utilizing Life Course to Examine Female Criminality - Hayden, Emily Ann (2015)
Employing a life-course framework, this research examines how various relationship typologies expands Sampson and Laub’s (2003) discussion of ‘marriage’ as a crucial mechanism involved in desistence. Moreover, recent contributions to life-course theory has identified a void in the literature in regards to how ‘turning points’ operate within female offenders. As such, this research fills those gaps by re-conceptualizing relationship typologies and focusing on the similarities between marriage and relationships. Two research questions are explored: If marriage is a turning point for crime, do non-marital relationships have a similar effect? If so, do different qualities and typologies of relationship status provoke similar mechanisms found within marriage? And second, if relationships status does have an effect in desisting from crime, how does the stability of the relationship vary in the likelihood of desistence? Through a mixed methods approach, a semi-structured interview and survey was administered to female detainees (n=27) at a medium-sized local jail/detention center. Results indicated that relationship typologies serve as a durable indicator to the onset and the desistence of criminal activity. Likewise, the results indicated a positive relationship between criminality and delinquent male counter-parts when defined as a significant other. Furthermore, female inmate’s cohabitation with a delinquent significant other was associated with poor relationship ‘stability’ and with illicit substance abuse lifestyles. Additional areas of concern surfaced, suggesting a need for further investigation for the interaction effects for illicit drug use, children, and history of abuse as factors that can both provoke and insulate female criminality